Dispersion Behavior of Gold-Nanocoated Dielectric Optical Fibers - P. K. Choudhury (Advances in Materials Science and Engineering)
Using a fairly rigorous approach, gold-nanocoated dielectric optical fibers are treated to evaluate the propagation characteristics corresponding to the transverse electric (TE) and hybrid EH modes, as supported by the guides with small and large dimensions. Situations with varying nanocoating thickness are considered for two different operating wavelengths. The results demonstrate a profound effect of the gold nanocoating on the propagation-related features—the number of existing modes decreases with increasing nanolayer thickness. Furthermore, the gold nanolayer also has effects on the modal propagation constants, which become more prominent with the increase in the order of modes. It has been found that, in fiber with smaller dimension, the EH11 mode hardly exhibits any effect due to the variation in existing nanolayer coating corresponding to 850 nm wavelength. Almost similar situations are observed for the TE01 mode in large core fiber operating at 1550 nm wavelength.